THE USE OF IE MATRIX AND SWOT MATRIKS IN SINGLE USE HAEMODIALYSIS SERVICE STRATEGY IN HOSPITAL X BANYUMAS DISTRICT - Margaretna, Nur Fitri; Rhomadon, Wahyu; Purwadhi, Purwadhi; Widjaja, Yani Restiani (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Hemodialysis (HD) is vital for managing patients with end-stage chronic kidney disease, ensuring their quality of life. Hospital X in Banyumas District, a private Type C hospital, has adopted single-use dialyzers to enhance safety and minimize infection risks. This study employs the Internal-External (IE) and SWOT matrices to develop strategies for improving the hospital's single-use HD services. Data were gathered through interviews, questionnaires, and hospital records, focusing on internal and external factors affecting HD services. The IE matrix indicates that the hospital is positioned for aggressive growth, suggesting strategies like market penetration, product development, and supply chain integration. The SWOT analysis identifies several strengths, such as BPJS support and a strategic location, while addressing weaknesses like limited promotional activities and dependency on vendors. Opportunities include government health policies and technological advancements, counterbalanced by threats such as economic instability and increased competition. Key recommendations include strengthening internal coordination, leveraging BPJS support, optimizing promotional strategies, and addressing vendor dependency through diversification. These strategies aim to enhance efficiency, attract more patients, and ensure competitive advantage. By aligning internal strengths with external opportunities, Hospital X can sustainably grow its HD services and improve overall healthcare delivery.